Customized Color Settings of Digitally Assisted Vitreoretinal Surgery to Enable Use of Lower Dye Concentrations During Macular Surgery - Park, Su Jin; Do, Jae Rock; Shin, Jae Pil; Park, Dong Ho (Frontiers in Medicine, 2022)
Purpose: This study evaluated the color contrast ratio (CCR) of the internal limiting membrane (ILM) using different color settings of digitally assisted vitreoretinal surgery (DAVS) with different indocyanine green (ICG) concentrations. Methods: This is a prospective comparative observational study. Consecutive patients that underwent 25G vitrectomy and ILM peeling using a standard operating microscope (SOM) (25 eyes), DAVS Ver. 1.1 (12 eyes), or DAVS Ver. 1.3 (13 eyes) were enrolled. The SOM and DAVS Ver. 1.1 groups used 0.075% ICG, and the DAVS Ver. 1.3 group used 0.025% ICG. In DAVS Ver. 1.1, macular CCR was compared between four different presets in the red, green, and blue channels: Default (Red (R) 100%, Green (G) 100%, and Blue (B) 100%); Preset 1 (R 20%, G 100%, B 100%); Preset 2 (R 80%, G 80%, B 100%), and Preset 3 (R 85%, G 100%, B 90%). In DAVS Ver. 1.3, macular CCR was evaluated using two different customized settings that modified the hue and saturation: Customized Setting 1 (R 86%, G 100%, B 100%, Hue +2°, Saturation 90%, Gamma 1.2) and Customized Setting 2 (R 90%, G 100%, B 100%, Hue +20°, Saturation 100%, Gamma 0.9). All patients underwent ophthalmologic examinations including BCVA at baseline and at 12 months. Results: In DAVS Ver. 1.1, macular CCR was highest in Preset 3 (P < 0.01). The CCR of Customized Setting 2 of DAVS Ver. 1.3 using 0.025% ICG did not differ from that of Preset 3 in DAVS Ver. 1.1 using 0.075% ICG. Furthermore, there was no significant difference in BCVA between the Customized Setting 2 of DAVS Ver. 1.3 with 0.025% ICG and the Preset 3 of DAVS Ver. 1.1 with 0.075% ICG groups at baseline and at 12 months (P > 0.05, respectively). Conclusion: Customized DAVS settings enabled surgeons to use a 3-fold lower ICG concentration in ILM peeling.